Aerobic training improves NAFLD markers and insulin resistance through AMPK-PPAR-α signaling in obese mice - Diniz, Tiego Aparecido; de Lima Junior, Edson Alves; Teixeira, Alexandre Abílio; Biondo, Luana Amorim; da Rocha, Lucas Ariel Fernandes; Valadão, Iuri Cordeiro; Silveira, Loreana Sanches; Cabral-Santos, Carol; de Souza, Camila Oliveira; Rosa Neto, José Cesar (Elsevier, 2021)
Liver steatosis is one of the main drivers for the development of whole-body insulin resistance. Conversely, aerobic training (AT) has been suggested as non-pharmacological tool to improve liver steatosis, however, the underlying molecular mechanism remains unclear. Therefore, the aim of this study was to analyze the effect of 8-weeks AT in non-alcoholic liver disease (NAFLD) outcomes in obese mice. Male C57BL/6 J wild type (WT) were fed with standard (SD) or high-fat diet (HFD) for 12-weeks. Another group fed with HFD underwent 8-weeks of AT (60% of maximum velocity), initiated at the 5th week of experimental protocol. We measured metabolic, body composition parameters, protein and gene expression inflammatory and metabolic mediators. We found that AT attenuates the weight gain, but not body fat accumulation. AT improved triacylglycerol and non-esterified fatty acid plasma concentrations, and also whole-body insulin resistance. Regarding NAFLD, AT decreased the progression of macrovesicular steatosis and inflammation through the upregulation of AMPK Thr172 phosphorylation and PPAR-α protein expression. Moreover, although no effects of intervention in PPAR-γ protein concentration were observed, we found increased levels of its target genes Cd36 and Scd1 in exercised group, demonstrating augmented transcriptional activity. AT reduced liver cytokines concentrations, such as TNF-α, IL-10, MCP-1 and IL-6, regardless of increased Ser536 NF-κB phosphorylation. In fact, none of the interventions regulated NF-κB target genes Il1b and Cccl2, demonstrating its low transcriptional activity. Therefore, we conclude that AT attenuates the progression of liver macrovesicular steatosis and inflammation through AMPK-PPAR-α signaling and PPAR-γ activation, respectively, improving insulin resistance in obese mice.
Keywords: AMPK and inflammation; Exercise; Hepatic steatosis; NAFLD